Key Compression and its Application to Digital Fingerprinting - Benaloh, Josh (Microsoft, 2001)
Digital fingerprinting technologies are becoming an increasingly important tool to protect valuable content and other intellectual property. This paper describes an efficient method whereby any watermarking technology can be utilized to construct digital fingerprints that can distinguish individual instantiations of protected data without requiring replication of the data. This technology enables large amounts of data to be selectively distributed to large numbers of people over a limited medium such as a broadcast channel or CD-ROM. An application of this technology – protection of motion pictures for in-flight entertainment systems – will be specifically discussed. Note: This is a reprint of an article that was originally submitted for publication in April 2001.